2021
DOI: 10.3390/atmos12020190
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Non-Exhaust Particulate Matter Traffic Emissions and the Impact of COVID-19 Lockdown at London Marylebone Road

Abstract: This research quantifies current sources of non-exhaust particulate matter traffic emissions in London using simultaneous, highly time-resolved, atmospheric particulate matter mass and chemical composition measurements. The measurement campaign ran at Marylebone Road (roadside) and Honor Oak Park (background) urban monitoring sites over a 12-month period between 1 September 2019 and 31 August 2020. The measurement data were used to determine the traffic increment (roadside–background) and covered a range of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 58 publications
4
42
0
Order By: Relevance
“…During the development process, the definition of a thermal load on the braking system, which is representative of the real operating conditions, was identified as a critical aspect. Since the release of nanoscale organic compounds was observed above a critical temperature threshold, a method was developed to limit the maximum temperatures [7][8][9][10]15,16]. The next step addressed the definition of an appropriate sampling setup.…”
Section: Brake Wear Particle Sampling and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development process, the definition of a thermal load on the braking system, which is representative of the real operating conditions, was identified as a critical aspect. Since the release of nanoscale organic compounds was observed above a critical temperature threshold, a method was developed to limit the maximum temperatures [7][8][9][10]15,16]. The next step addressed the definition of an appropriate sampling setup.…”
Section: Brake Wear Particle Sampling and Measurementmentioning
confidence: 99%
“…These include particulate brake wear [5]. Since most of the emitted particles belong to the size classes of particulate matter (≤10 µm) and differ significantly in their physico-chemical properties from automotive exhaust emissions, this source is of particular relevance to human health and is therefore the focus of scientific studies [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During the lockdown periods, a 32% decrease in the traffic volume on the Marylebone road and 15% increase in the average speed were observed. Thus, it has been revealed that vehicle emissions have also decreased [29].…”
Section: Literature Review On Vehicular Pollutant Emission Pre and Post Pandemicmentioning
confidence: 99%
“…Zn could be released into the environment from a variety of anthropogenic sources, such as coal combustion [14], nonferrous metal smelting [11] and traffic emissions [15,16]. However, there has been little research on the atmospheric emissions and mass flow of Zn within the cement plants (CPs) with respect to its low boiling point (907 • C) comparing to the high-temperature calcination (1450 • C) process [17,18], which produces clinker and is a key part of the whole cement production process.…”
Section: Introductionmentioning
confidence: 99%